Differential Leukocyte Count Responses Post Injection of Duffy-binding-like Domain-2β of PfEMP1 Recombinant Protein in Wistar Rat - Zahniar, Zahniar; Sulistyaningsih, Erma; Rachmania, Sheilla; Dewi, Rosita; Kusuma, Irawan Fajar (Medical Laboratory Technology Journal, 2025)
Malaria due to Plasmodium falciparum causes a high mortality rate, and vaccination is a valuable approach to control it. One malaria vaccine candidate is Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP1), specifically Duffy binding-like 2β (DBL2β) domain (DBL2β-PfEMP1), which has a vital role in severe malaria pathogenesis. The DBL2β-PfEMP1 recombinant protein is immunogenic. This study aimed to investigate the immune response of DBL2β-PfEMP1 protein by analyzing the differential leukocyte count. Twenty-three rats were randomly divided into control and five treatment groups. Rats were injected on days 0, 21, and 42 with a physiological solution of 0.9% NaCl, adjuvant, DBL2β-PfEMP1 protein, and each mixture of DBL2β-PfEMP1 protein with doses of 150, 300, and 450 µg/200gBW and adjuvant. Blood was collected on day 56 and prepared for differential leukocyte count examination with a visual microscopic examination by two expert observers. The results showed that DBL2β-PfEMP1 recombinant protein and adjuvant increased the eosinophils and neutrophils but decreased monocytes and lymphocytes and did not affect the basophils. Statistical analysis showed significant differences between groups for eosinophils (between control and DBL groups; Adj and DBL groups; DBL and other groups except DBL150+adj) and monocytes (between control and all doşe groups with adjuvant; DBL and all doşe groups with aduvant), but not for basophils, neutrophils, and lymphocytes. In conclusion, the serial injection of DBL2β-PfEMP1 recombinant protein showed different responses in each leukocyte cell type. Further analysis by time-series differential leukocyte count examination will be essential to determine the responses of each type of leukocyte to support the research on malaria vaccine development.